Aerodynamic Phenomena of Controlling Passive Flow of a Time‐Independent Ground Vehicle Under the Scope of Optimally Slanted Rear Wing‐Spoiler Combination - Abyaz Abid (Engineering Reports)
ABSTRACT Notwithstanding the abundance of different expository efforts by the engineers and scientists of the aerodynamic—transonic domain for the ever‐beseeched question of whether a supercar needs a rear spoiler or a rear wing, the query requires further exploration to come to any satisfactory conclusion. This state‐of‐the‐art bottleneck area is considered as the prime motivation of the paper as it seeks to investigate the aerodynamic phenomena of a notchback type supercar configuration with two different series of modifications—one with a rear spoiler attachment and the other one with a rear wing attached. A simplified Nissan Skyline GT34R CAD model is taken as the base ground vehicle for the computational study while the slant angles of both the rear wing and rear spoiler are changed within the range of 10° to 45°. RANS based k‐omega SST turbulence model is used to find the optimal slant angles for the corresponding rear wing and spoiler in terms of drag and lift coefficients, drag and lift force and rolling moment. The modified models with optimally slanted rear wing and rear spoiler along with the base configuration are inspected under different visualization techniques for understanding the aerodynamic phenomena. Contour and vector plots reveal that rear wing attached model has the maximum pressure drop along and over its body showing a sharp increase of 13.7% when compared with the rear spoiler attached model. Aftereffects show that both the turbulent intensity and Y+ wall shear stress is found to be most economical for the rear spoiler attached model, approximately 1.52% and 0.98% less than the base notchback model. Considering, overall aerodynamic performance of all the three proposed notchback type supercar configurations—the one with a rear spoiler attachment is found to be the most equipped one to integrate into future research.